The Impact Of Mobile Banking Customer Experience On Loyalty Among Millennials In South Africa - Ncube, Justice (Department of Information Systems, 2021)
The modern environment of pervasive interconnectedness via mobile devices and services makes it important to understand the nature of customer-bank interactions and relationships. Businesses that offer mobile banking are trying to provide their customers with improved customer service and experiences. The objective of this study is to examine how customer experience of mobile banking influences loyalty towards the bank. This study focuses on the millennials in South Africa. Banks need to remain competitive in the ever-changing business environment. Millennials are one of the largest customer segments with a large digital and mobile appetite; as a result, they form a natural target for banks. To increase their customer base, banks need to ensure that their customer experience strategy caters for these young customers in accordance with their expectations. However, customer experience within mobile banking is under researched. Previous studies in this research area have focused on customer experience in traditional banking context. This study tries to fill the gap by exploring the factors that influence customer experience in mobile banking and also understand how this experience influences customer loyalty to their bank. Considering this, a broad literature review was done that revealed the factors that influence mobile customer experience. Based on literature a conceptual model was developed and this model was used a framework for investigating the research problem. This study used a mixed methods strategy and collected data from 344 mobile banking users via an online survey questionnaire and further, 10 semi-structured interviews were also conducted. The research hypotheses were tested through regression analysis and this resulted in 4 out of 8 research hypotheses being supported. Thematic analysis was used for both the open-ended questions in the survey and the 10 interviews. The results showed that convenience, ease of use and customization are the most significant factors that influence customer experience in mobile banking, whereas the customer experience was in turn found to have a significant influence on customer loyalty. Through conducting this research on millennials in South Africa, this study has expanded the knowledge of mobile banking research in the country. A valuable contribution was made by this study, as this study gave better insight into the factors that significantly influence the customer's experience of millennials in mobile banking. This study recommends that, it is important that banks as well as other firms that offer mobile banking offer a mobile app that is convenient and lets customers to perform their activities in a flexible way in their own time, easily and in a customizable manner. Therefore, should banks implement this study's recommendations it will be beneficial for them as this will result in increased loyalty of their millennial mobile banking customers.